Prioritizing Improvement Projects of EFQM by Fuzzy Group AHP and Try-Success Matrix- The Case of a Manufacturing Industry - Seyed javad Mosa kassamy; Mohammad Rokni; Amir Hossein Okhravi (مدیریت تولید و عملیات, 2012)
The aim of this paper is to prioritize projects by a new approach . For prioritizing EFQM projects , self-assessment is conducted by industry experts and then , improve ment projects are determined . For these projects, “prioritizing” is the main problem in organizations. Because of resource constraints, those projects should be selected and implemented that provide most benefits. Selecting the appropriate indicators, such as " quantity of required resources", " impact on stakeholders" and " p robability of project success" can significantly influence selection of projects. These indicators have been considered in the Try-Success matrix. Also, since each project is depend ed on the EFQM’s criteria, the weights of the criteria have been localized . In the designed software of this study, the scoring mechanism is based on Try-Success matrix, and the local weights are determined by Fuzzy-group AHP. In this paper , the application of software in prioritization of projects has been also addressed. T he output of this approach together with software and investigation, are the determined projects that have higher priorities and provide considerable improvement to the industry .